Patients' Experience to MRI Examinations—A Systematic Qualitative Review With Meta-Synthesis - Nieto Alvarez, Isabel; Madl, Janika; Becker, Linda; Amft, Oliver (Journal of Magnetic Resonance Imaging, 2024)
Background: Patients often mention distress, anxiety, or claustrophobia related to MRI, resulting in no-shows, disturbances of the workflow, and lasting psychological effects. Patients' experience varies and is moderated by socio-demographic aspects alongside the clinical condition. While qualitative studies help understand individuals' experiences, to date a systematic review and aggregation of MRI individuals' experience is lacking. Purpose: To investigate how adult patients experience MRI, and the characterizing factors. Study Type: Systematic review with meta-aggregation and meta-synthesis. Population: 220 patients' reported experience of adults undergoing clinical MRI and 144 quotes from eight qualitative studies. Assessment: Systematic search in PubMed, Scopus, Web of Science, and PsycInfo databases according to the PRISMA guidelines. For quality appraisal, the Joanna Briggs Institute (JBI) tools were used. Convergent segregated approach was undertaken. Data Analysis: Participant recruitment, setting of exploration, type of interview, and analysis extracted through Joana Briggs Qualitative Assessment and Review Instrument (JBI QARI) tool. Meta-synthesis was supported by a concept map. For meta-aggregation, direct patient quotes were extracted, findings grouped, themes and characterizing factors at each stage abstracted, and categories coded in two cycles. Frequency of statements was quantified. Interviews' raw data unavailability impeded computer-aided analysis. Results: Eight articles out of 12,755 initial studies, 220 patients, were included. Meta-aggregation of 144 patient quotes answered: (1) experiences before, at the scanning table, during, and after an MRI, (2) differences based on clinical condition, and (3) characterizing factors, including coping strategies, look-and-feel of medical technology, interaction with professionals, and information. Seven publications lack participants' health literacy level, occupation, and eight studies lack developmental conditions, ethnicity, or country of origin. Six studies were conducted in university hospitals. Data Conclusion: Aggregation of patients' quotes provide a foundational description of adult patients' MRI experience across the stages of an MRI process. Insufficient raw data of individual quotes and limited socio-demographic diversity may constrain the understanding of individual experience and characterizing factors. Level of Evidence: 1. Technical Efficacy: Stage 5.
CRIS-Team Scopus Importer:2024-04-12
Keywords: anxiety; information; magnetic resonance imaging; patient experience; patient-centered care